Food Insecurity and Anthropometry in Adolescents: A Literature Review - Dewi, Nikmah Utami; Nurulfuadi, Nurulfuadi; Aiman, Ummu; Diah Ayu Hartini; Fendi Pradana; Bohari, Bohari (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: The increased risk of malnutrition is affected by food insecurity. Studies in adolescents still show mixed results. AIM: This article aimed to evaluate the association between food insecurity and anthropometry measurements in studies involving adolescents. MATERIALS AND METHODS: The databases used to obtain the literature were PubMed, ScienceDirect, MEDLINE, and PubMed Central. The keywords used were food security, food insecurity, hunger, malnutrition, obesity, adolescence, adolescents, teenagers, teens, and youth in studies published from 2010 to 2019. A total of 12 articles were used in this review. RESULTS: The association between food insecurity and the incidence of malnutrition in adolescents in various regions is still diverse. Food insecurity had a negative correlation with BMI-for-age in three studies (33.3%), but one study (11.1%) showed the opposite result. Food insecurity was positively related to low height-for-age (stunting) in 50% of studies, while five other studies (55.6%) showed that food insecurity was not related to BMI-for-age or weight-for-age. Three studies (50%) showed that there was no association between food insecurity and height-for-age. CONCLUSION: Longitudinal studies, such as Cohort studies, need to be conducted to ensure the actual relationship between food insecurity and nutritional status in various regions.